Process Features Discovery Of LowPressure Layers (Eurasian Research Bulletin, 2024)
This article provides information on the complexity of drilling into low-pressure formations and the use of balanced pressure drilling technologies during drilling, as well as the rate of displacement of the gas-liquid mixture and the causes of adverse effects.